ENTREPRENEURSHIP SUPPORT OF ECONOMIC GROWTH IN CHINA (I) - IACOB, Severian Vladut (Ecoforum Journal, 2015)
Economic growth over the past three decades in China has captured the interest of the whole world. Many nations, governments, business and science look admiringly to "Chinese miracle". The performance of this country is the more remarkable as it includes, besides the effort to go beyond a developing country and the transition from a communist economy to the market economy. "Chinese development model", whereof spoken more and more in this period is unclear due to some nuances not really classical approach to development paradigm, which focuses on promoting democracy, human rights privatization, liberalization and the fight against corruption. Through the new model, some authors, starting from high authority of the state over property and finances, assigns to it a key role in economic growth. From their point of view, the strong boom of the private sector in China is the result of the opening provided by the state and not as a prerequisite for development. This perception is unpopular but other authors who argue that "the Chinese success had as basic ingredients exactly private entrepreneurship, private property, financial and even political reforms, though not always apparent at first glance." This study made ​​a brief foray into Chinese entrepreneurship development, opening new possibilities of deepening towards understanding how it managed to contribute to the development and growth of the country.